Empowering Sustainability: Localizing SDGs through Solar Energy in Central Java - Rudiany, Novita Putri (Global and Policy Journal of International Relations, 2026)
This study analyzes how provincial governments can contribute to achieving the Sustainable Development Goals (SDGs) through renewable energy development, using the case of solar power plants in Central Java Province. Drawing on the institutional capacity framework proposed by Salvador and Sancho (2021), the research examines four dimensions—strategic, analytical, organizational, and collaborative capacity—to understand how local governments localize SDG 7, which aims to ensure access to affordable, reliable, sustainable, and modern energy for all. Employing a qualitative approach, the study combines primary data from interviews with key provincial stakeholders and secondary data from official reports, policy documents, and academic literature. The findings show that Central Java, one of Indonesia’s first solar-producing provinces, achieved a 13.38% renewable energy mix in 2021 through systematic rooftop solar initiatives in government offices, schools, and industries. This demonstrates that strong strategic planning, data-based policy design, and stakeholder collaboration enhance local SDG implementation. However, institutional coordination remains a significant challenge. The study concludes that provincial governments, due to their proximity to communities, hold crucial potential in advancing national sustainability targets, emphasizing the need for stronger inter-agency collaboration to improve renewable energy governance.